The Effectiveness of e-Learning, Learning Styles, Prior Knowledge, and Internet Self Efficacy in Business Mathematics Courses - Azis, Yunia Mulyani; Leatemia, Meiti (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
The purpose of this study is to analyze the effectiveness of e-learning associated with learning style variables, prior knowledge, and internet self efficacy (ISE) in the Business Mathematics course. The research method uses descriptive statistics and correlations, where the learning styles studied are visual, auditory, reading, and kinesthetic. The results and conclusions of this study are (1) the majority of respondents have a visual learning style, (2) simultaneously learning styles, prior knowledge, and internet self-efficacy affect learning outcomes in e-learning strategies, (3) partially initial knowledge and internet self efficacy does not affect learning outcomes, and (4) The effectiveness of e-learning Business Mathematics is achieved in respondents with visual learning styles, because respondents with this learning style tend to have high internet self-efficacy, even though respondents have low prior knowledge of MathematicsTujuan dari penelitian ini adalah untuk menganalisis efektivitas e-learning dikaitkan dengan variabel gaya belajar, pengetahuan awal, dan internet self efficacy (ISE) pada mata kuliah Matematika Bisnis. Metode penelitian menggunakan statitika deskriptif dan korelasi, dimana gaya belajar yang diteliti adalah visual, auditory, reading, dan kinestetik. Hasil dan  kesimpulan penelitian ini adalah (1) mayoritas responden mempunyai gaya belajar visual, (2) secara simultan gaya belajar, pengetahuan awal, dan internet self efficacy mempengaruhi hasil belajar dalam strategi e-learning, (3) secara parsial pengetahuan awal dan internet self efficacy tidak mempengaruhi hasil belajar, dan (4) Efektivitas  e-learning Matematika Bisnis tercapai pada responden dengan gaya belajar visual, karena responden dengan gaya belajar tersebut cenderung mempunyai internet self efficacy yang tinggi, walaupun responden memiliki pengetahuan awal Matematika yang rendah.